2004
DOI: 10.1158/0008-5472.can-04-0562
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Agent Molecular Targeting of the Epidermal Growth Factor Receptor (EGFR)

Abstract: Molecular inhibition of epidermal growth factor receptor (EGFR/ HER1) signaling is under active investigation as a promising cancer treatment strategy. We examined the potency of EGFR inhibition achieved by combining anti-EGFR monoclonal antibody and tyrosine kinase inhibitor, which target extracellular and intracellular domains of the receptor, respectively. We specifically studied the combination of cetuximab (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
219
3
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 358 publications
(232 citation statements)
references
References 14 publications
8
219
3
2
Order By: Relevance
“…It must be underlined that, when examining the different cell lines which were explored in these two latter studies, the supra-additivity of the dual EGFR targeting was not found in all explored cell lines; these cell lines differed markedly between them for the EGFR content. Differences in intrinsic EGFR tumoral expression may modulate the final impact of the dual EGFR targeting and explain the differences between the present conclusions and those reported by the two other groups (Huang et al, 2004;Matar et al, 2004). In the present study, the infra-additive impact on cell survival was sustained by the changes in cleaved PARP, a faithful molecular indicator of apoptotic process, showing that C225-ZD1839 caused less apoptosis than ZD1839 alone.…”
Section: Discussioncontrasting
confidence: 69%
See 2 more Smart Citations
“…It must be underlined that, when examining the different cell lines which were explored in these two latter studies, the supra-additivity of the dual EGFR targeting was not found in all explored cell lines; these cell lines differed markedly between them for the EGFR content. Differences in intrinsic EGFR tumoral expression may modulate the final impact of the dual EGFR targeting and explain the differences between the present conclusions and those reported by the two other groups (Huang et al, 2004;Matar et al, 2004). In the present study, the infra-additive impact on cell survival was sustained by the changes in cleaved PARP, a faithful molecular indicator of apoptotic process, showing that C225-ZD1839 caused less apoptosis than ZD1839 alone.…”
Section: Discussioncontrasting
confidence: 69%
“…Taken together, the above-mentioned arguments provided justification for testing the combination of C225 and ZD1839. A recent study by Huang et al (2004) examined the antitumour effects resulting from this dual combination more marked tumour regressions were observed with the combination of ZD1839 and C225 in mice bearing a human lung cancer xenograft. Another recent study by Matar et al (2004), based on both in vitro and in vivo data, led to similar conclusions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At least three independent groups, (Johns et al, 2003;Huang et al, 2004;Matar et al, 2004;Perera et al, 2005). In further support of this approach we have observed promising clinical activity of the combination of an EGFR TKI and cetuximab, a monoclonal antibody directed at the extracellular domain of the EGFR .…”
Section: Lapatinib-induced Stabilization and Accumulation Of Her2mentioning
confidence: 65%
“…Some preclinical studies (Huang et al, 2004;Matar et al, 2004) but not all showed synergistic effect, but solid clinical data are lacking.…”
Section: Combination Of Targeted Therapiesmentioning
confidence: 99%